Assessment of the use of the laryngeal tube for cardiopulmonary resuscitation in a manikin - Genzwürker, Harald; Finteis, Thorsten; Slabschi, D.; Gröschel, Joachim; Ellinger, Klaus (Resuscitation, 2001)
During 60 3-min CPR sequences, the face mask, laryngeal tube and tracheal tube were compared using an Ambu Megacode Trainer. Ten 3-min sequences each were performed for both a combination of the face mask and laryngeal tube with a bag-valve device (compression-ventilation ratio 5:1). With continuous chest compressions, ten 3-min CPR sequences each were performed for a combination of the laryngeal tube and tracheal tube with a bag-valve device and ten 3-min CPR sequences each for a combination of the laryngeal tube and tracheal tube with an automatic transport ventilator. Signs of gastric inflation occurred only with the face mask. Ventilation with the laryngeal tube was significantly better than with the face mask and comparable to the tracheal tube during ventilation with the bag-valve device and with the automatic transport ventilator. Chest compressions caused a significant decrease in tidal volumes during ventilation with the automatic transport ventilator. The findings of this study support the idea of the laryngeal tube as a new adjunct for emergency airway management, but will have to be verified during clinical practice.